(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2020)
Research relating to the definition of man is an activity that has engaged Kant since the beginning of his philosophy and, in this regard, an important contribution can be drawn from the theory of the sublime. The sublime is one of the undisputed protagonists of the Critique of the power of judgement, but its role is not limited to the completion of aesthetic theory, as it also stands out for its ability to render an exhaustive portrait of man in Kant’s philosophy.